Parasitism of Trichogramma and predation of Chrysoperla on Compsus viridivittatus eggs, a Vitis vinifera pest, under laboratory conditions - Pinzón-Hamón, Diego Alonso; Martínez-Osorio, John Wilson; Castro-López, Mayerly Alejandra (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The parasitic potential of Trichogramma exiguum and Trichogramma pretiosum and the predatory effect of Chrysoperla carnea were evaluated on Compsus viridivittatus eggs, an insect pest in grape fields in Boyaca, Colombia. The T. exiguum and T. pretiosum tests used 240 eggs groups exposed to 0, 15, 30 and 45 parasitoids densities. In the C. carnea test, a second instar larva was placed with prey densities of 80, 160 and 240 C. viridivittatus eggs. A completely randomized design was used under laboratory conditions (18±2°C and 60±5% RH). In the trials with T. exiguum and T. pretiosum, the highest percentages of parasitism were obtained with the 45 parasitoid density (69.4% and 82.5%, respectively). It was established that T. pretiosum was more effective in the parasitism of C. viridivittatus than T. exiguum, resulting in larvae emergence under 13% and parasitism over 70%. The test with C. carnea showed that the highest consumption percentage (85.8%) was obtained with the 80 C. viridivittatus egg density. There was no emergence of parasitoids from the eggs parasitized by T. exiguum and T. pretiosum, probably because of the environmental conditions and/or C. viridivittatus host intrinsic characteristics. The tested entomophagous species showed over 50% C. viridivittatus egg mortality, suggesting that they can be used in future field tests in grape vine crops in order to observe their potential in C. viridivittatus biological control programs in Boyaca.